Microwave co-pyrolysis of kitchen food waste and rice straw: Effects of susceptor on thermal, surface, and fuel properties of biochar - Nyambura, Samuel Mbugua; Li, Chao; Li, Hua; Xu, Jialiang; Wang, Jialiang; Zhu, Xueru; Feng, Xuebin; Li, Xiaolin; Bertrand, Gbenontin V; Ndumia, Joseph Ndiithi; Chin, Bridgid Lai Fui (2023)
In this research, microwave co-pyrolysis of kitchen food waste and rice straw under no susceptor, biochar susceptor, and ZnCl2 susceptor was undertaken to investigate the synergistic effects on biochar properties for energy application. The results showed that co-pyrolysis and the addition of susceptors significantly positively affected the thermochemical, fuel, thermal, and surface properties of biochar. Regardless of the susceptor conditions, blending kitchen food waste with rice straw effectively decreased the biochar yield (up to 2.14% and 6% for biochar and ZnCl2 susceptors, respectively) and abundance of –OH functional groups, but improved the chars’ thermal stability and surface area. Biochar produced at a ratio of 1:1 under ZnCl2 exhibited acceptably low ash content coupled with high higher heating value (20.550 MJ/kg), high energy yield (55.944%), and high fuel ratio (≤5.267) thereby demonstrating excellent fuel properties. These findings highlight the exceptional potential of co-pyrolytic biochar as a sustainable and eco-friendly energy source.